2010
DOI: 10.5026/jgeography.119.826
|View full text |Cite
|
Sign up to set email alerts
|

Surface Rupture of the 2008 Iwate-Miyagi Nairiku Earthquake Observed at Oshu and Ichinoseki Cities, Iwate Prefecture, Northeast Japan

Abstract: The 2008 Iwate-Miyagi Nairiku earthquake (Mw 6.9) struck an area where no active fault was known prior to the earthquake. The earthquake was shallow and large enough to produce scattered and discontinuous surface ruptures. To better understand the source processes and seismotectonic setting of the earthquake, we mapped the coseismic surface ruptures observed at Oshu and Ichinoseki Cities, Iwate Prefecture. The NNE-to NNW-trending surface ruptures appeared at three localities: (1) between Mochikorobashi and Och… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…1) measured a vertical acceleration of 3.95 g (Aoi et al 2008). Coseismic surface displacements of up to 1.2 m have been measured by InSAR (Takada et al 2009) and major surface ruptures were also reported (Tsutsumi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1) measured a vertical acceleration of 3.95 g (Aoi et al 2008). Coseismic surface displacements of up to 1.2 m have been measured by InSAR (Takada et al 2009) and major surface ruptures were also reported (Tsutsumi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…InSAR measurements revealed coseismic surface displacements of up to 1.2 m caused by the earthquake [ Takada et al , 2009]. The surface ruptures associated with the earthquake were studied by Tsutsumi et al [2010]. The earthquake triggered an aseismic slow slip event on the Detana fault, northeast of the Iwate‐Miyagi Nairiku earthquake fault zone [ Iinuma et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The geology of the Hanokidachi region comprises Tertiary sedimentary rocks, and is similar lithologically to the Izumozaki region. The Hanokidachi region suffered fewer landslides than the Kurikoma-dam region, although clear surface ruptures had been investigated (Tsutsumi et al, 2010).…”
Section: Study Areas and Datamentioning
confidence: 99%